2009
DOI: 10.4161/derm.1.6.10970
|View full text |Cite
|
Sign up to set email alerts
|

An estimate of the survival benefit of improving vitamin D status in the adult German population

Abstract: IntroductionVitamin D is well known for its effects on calcium and bone metabolism. Vitamin D deficiency results in rickets in infants and small children and in osteomalacia and osteoporosis in adults. However, recent advances in the understanding of vitamin D have revolutionized our view of this old nutritional factor and suggested that it has much wider effects on the body than ever believed before. Major reasons for this situation are insufficient skin exposure to solar ultraviolet B radiation together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…Italy has prevalence levels of 17% below 12 ng/ml in winter in the south (Carnevale et al, 2001) and one-third of healthy women o20 ng/ml in the north (Adami et al, 2009), which is very similar to our prevalence. Germany has lower levels of vitamin D than in our study, the prevalence of vitamin D insufficiency in the German National Health Interview and Examination Survey was 450% in the general population and 60% in children (Hintzpeter et al, 2008a, b), with the DEVID (The vitamin in Deutschland) study reporting mean levels of 41 ± 22 nmol/l (Zittermann et al, 2009). In the British population, the prevalence is greater than in Spain, Hyppönen and Power (2007) reported a prevalence of hypovitaminosis D o75 nmol/l in 87.1% of participants in winter and in 60.9% in summer.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Italy has prevalence levels of 17% below 12 ng/ml in winter in the south (Carnevale et al, 2001) and one-third of healthy women o20 ng/ml in the north (Adami et al, 2009), which is very similar to our prevalence. Germany has lower levels of vitamin D than in our study, the prevalence of vitamin D insufficiency in the German National Health Interview and Examination Survey was 450% in the general population and 60% in children (Hintzpeter et al, 2008a, b), with the DEVID (The vitamin in Deutschland) study reporting mean levels of 41 ± 22 nmol/l (Zittermann et al, 2009). In the British population, the prevalence is greater than in Spain, Hyppönen and Power (2007) reported a prevalence of hypovitaminosis D o75 nmol/l in 87.1% of participants in winter and in 60.9% in summer.…”
Section: Discussionmentioning
confidence: 79%
“…Vitamin D deficiency is common, though its prevalence varies depending on the characteristics of the study population (Carnevale et al, 2001;Isaia et al, 2003;Hyppönen and Power, 2007;Boüüaert et al, 2008;Hintzpeter et al, 2008a, b;Adami et al, 2009;Annweiler et al, 2009;Zittermann et al, 2009;Lips, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The DEVID (De Vitamin in Deutschland) study is an investigation performed in 1343 adult individuals who had an outpatient visit with their general practitioner [16] [17], congestive heart failure patients [18], organ transplanted patients [19], and obese patients [20]. In a small study in female students of childbearing age [17], it has been demonstrated that mean winter values of circulating 25(OH)D were only slightly above the deficiency range (33 nmol/L).…”
Section: Vitamin D Status In Germanymentioning
confidence: 99%
“…Improving vitamin D status might thus be a promising public health strategy for increasing survival. According to conservative estimations, at least 2.2% of all deaths or 18 300 lives annually could probably be saved by achieving 25(OH)D concentrations of at least 75 nmol/L in the entire German population [16].…”
Section: Vitamin D Deficiency and Mortalitymentioning
confidence: 99%
“…We calculated an associated mortality rate of 18,000 lives lost each year [166]. The EPOCA theory submitted here is one causal explanation for this large number.…”
Section: Novel Cancer Preventionmentioning
confidence: 99%